Trends in hepatocellular carcinoma in Louisiana, 2005-2015 - John M. Lyons, III; Denise M. Danos; Lauren Maniscalco; Yong Yi; Xiao-Cheng Wu; Quyen D. Chu (Elsevier, 2022)
Introduction: Louisiana has one of the highest incidence and mortality rates of hepatocellular carcinoma (HCC) in the nation. The aim of this study was to analyze the trends in HCC incidence and relative survival rates in Louisiana and compare them with corresponding national rates, which can be used to formulate strategies to improve Louisiana HCC outcomes. Methods: Data on primary invasive HCC diagnosed in patients 20 years or older between 2005 and 2015 were obtained from the Surveillance, Epidemiology and End Results (SEER) program and Louisiana Tumor Registry. Time trends in HCC incidence and 12-month relative survival were analyzed using Joinpoint regression. Case characteristics were compared on 2 time periods (2005-2009 and 2010-2015) using Chi-squared tests. Cause-specific survival was analyzed via log-rank and multivariable Cox proportional hazard model. Results: Over the study period, the average annual percent change (AAPC) in age-adjusted HCC incidence in Louisiana was nearly double that of the national estimate, 6% (95% CI: 4.7, 7.3) compared to 3.1% (95% CI: 2.4, 3.7). 12-month relative survival among HCC patients in Louisiana was 40.7% (95% CI: 38.9, 42.4) which was significantly less than the US rate of 48.2% (95% CI: 47.8, 48.6). Relative survival did improve in Louisiana from 2000 to 2015 at a rate similar to that of the US (AAPC (95% CI): 2.9 (0.7, 5.2) vs. 2.7 (2.3, 3.1), p = 0.8). In multivariable survival analysis, factors amongst Louisianans associated with worse survival were older age at diagnosis, advanced stage of disease, and lack of surgical therapy. Conclusion: The incidence of HCC continues to rise more dramatically in Louisiana than in the US. While some modest improvements in HCC survival have been realized, outcomes remain dismal. Future work identifying the most at-risk populations are needed to inform statewide public health initiatives.